Addressing unmet needs in understanding asthma mechanisms: From the European Asthma Research and Innovation Partnership (EARIP) Work Package (WP)2 collaborators. Issue 5 (2nd May 2017) - Edwards, Michael R.; Saglani, Sejal; Schwarze, Jurgen; Skevaki, Chrysanthi; Smith, Jaclyn A.; Ainsworth, Ben; Almond, Mark; Andreakos, Evangelos; Belvisi, Maria G.; Chung, Kian Fan; Cookson, William; Cullinan, Paul; et al.
Asthma is a heterogeneous, complex disease with clinical phenotypes that incorporate persistent symptoms and acute exacerbations. It affects many millions of Europeans throughout their education and working lives and puts a heavy cost on European productivity. There is a wide spectrum of disease severity and control. Therapeutic advances have been slow despite greater understanding of basic mechanisms and the lack of satisfactory preventative and disease modifying management for asthma constitutes a significant unmet clinical need. Preventing, treating and ultimately curing asthma requires co-ordinated research and innovation across Europe. The European Asthma Research and Innovation Partnership (EARIP) is an FP7-funded programme which has taken a co-ordinated and integrated approach to analysing the future of asthma research and development. This report aims to identify the mechanistic areas in which investment is required to bring about significant improvements in asthma outcomes. This manuscript describes a state-of-the-art view of the mechanisms involved in asthma onset, asthma progression and asthma exacerbations and is an outcome of the European Asthma Research and Innovation Partnership (EARIP:www.earip.eu ). Readers are also referred to companion EARIP reports including a report describing the vision and call to action resulting from the EARIP project, to explore pathways for optimising asthma research in Europe [1], a report on national and regional asthma programmes in Europe [2] and an editorial on building the case for more investment in asthma research in Europe [3]. The European Asthma Research and Innovation Partnership (EARIP) prioritises unmet needs in asthma mechanisms research http://ow.ly/zroI30a9MUs